The Indonesian National Sports Committee (KONI) Manages, Implements, and Supervises Leading Sports Branches in Sinjai Regency - Andi Baso Husain; Ade Yuni Sahruni (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The Sinjai Regency has great potential to achieve proud athletic achievements. However, this potential is hindered by problems such as inappropriate management, poor coordination between relevant parties, and lack of monitoring of sports development programs. Therefore, this research aims to examine the superior sports management of KONI in Sinjai Regency to improve the achievements of superior sports in Sinjai Regency. Materials and methods. This research is a quantitative study with a descriptive research design. The sampling method used was simple random sampling with cluster sampling. A total of 50 people from the Sinjai Regency KONI organization participated in the study, including 28 administrators, 2 coaches, and 20 athletes. Results. Following the completion of data processing, the research findings indicated that the management of KONI's flagship sports branch in Sinjai Regency received an implementation test score of 31.94, categorizing it within the less reliable classification. Furthermore, the supervision test score of 33.00 also fell within the less reliable category. Conclusion. According to the research findings, KONI's management of its top sports division is currently lacking. The average score for implementation management falls below the medium category, indicating room for improvement. Conversely, the supervisory management of KONI's flagship sports branch is highly effective, as the average score exceeds the strong category.